Mapping of the Retrotransposable Elements Rex1 and Rex3 in Chromosomes of Eigenmannia (Teleostei, Gymnotiformes, Sternopygidae) - De Sene, Viviani F. [UNESP]; Pansonato-Alves, José C. [UNESP]; Ferreira, Daniela C.; Utsunomia, Ricardo [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Karger Publishers, 2015)
Transposable elements constitute a remarkable fraction of the eukaryote genome and show particular capacity to move and insert in specific regions of the genome. This study identified the retrotransposable elements Rex1 and Rex3 in the genomes of 6 cytotypes of Eigenmannia. The sequences were isolated by PCR, sequenced and physically mapped in the chromosomes of these cytotypes, aiming to investigate the organization and distribution of these elements in this fish group, mainly in the sex chromosomes. The FISH physical mapping revealed that both Rex1 and Rex3 elements are dispersed in small clusters throughout the chromosomes of all cytotypes analyzed. However, conspicuous blocks occur in several samples, including an accentuated accumulation of the Rex3 element in X1 and X2 chromosomes of Eigenmannia sp. 2 and in the X chromosome of E. virescens. The accumulations are coincident with heterochromatin-rich regions, suggesting that Rex3 played a role in the differentiation process of the sex chromosomes.
Keywords: Heterochromatin; Molecular markers; Retrotransposons; Rex1; Rex3; Sex chromosomes; Transposable elements